The Application of the Demonstration Method Assisted by Video Media in Information and Communication Technology Learning - Ekaria Wati Giawa (Jurnal Pendidikan Vokasi Indonesia, 2023)
This study aims to examine the improvement of student engagement and participation in teaching and learning activities through the implementation of the demonstration method assisted by video media in the subject of Information and Communication Technology (ICT). The research was conducted on eleventh-grade students of SMA Nasrani 3 Medan. The method used is Classroom Action Research (CAR), which was carried out in two cycles. Each cycle consisted of four stages: (1) Planning, (2) Action Implementation, (3) Observation, and (4) Reflection. Video media was used as a supporting tool in practicum activities to provide more concrete visualizations of the material being taught. The results showed a significant increase in students' learning activity in each cycle. Students became more enthusiastic, focused, and actively involved in the learning process, especially during practical sessions. These findings indicate that the application of the demonstration method supported by video media can be an effective strategy to enhance student participation in ICT learning.